Al-Af’al al-Kalamiyyah fi Taqdim al-Nashaih li al-Nisa fi Kitab Ya Binti li al-Syaikh Ali al-Thanthawi: Dirasah Tahliliyyah Uslubiyyah Tadawuliyyah/Speech Acts in The Delivering Advice to Women in The Book Ya Binti by Ali al-Thanthawi: Pragmatic Stylistic Analysis Study - Nur Hasyikin; Muhsin Ahmad; Andi Abdul Hamzah (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2025)
Ali al-Thanthawi's book Ya Binti is an important work rich in advice for women, but has not been widely studied from a stylistic and pragmatic perspective. This research aims to analyze the language style and forms of speech acts and their functions in the book Ya Binti based on what was stated by Abrams and Harpham. This study focuses on four stylistic aspects: phonology, lexical, syntactic, and rhetoric. Furthermore, a pragmatic approach is used to explore the forms and functions of speech acts contained in the book Ya Binti. This research is a literature study and uses a qualitative descriptive analysis method. The results show that Ya Binti is a work rich in variations in language style and speech acts. Every stylistic element from phonology, lexical, syntax to rhetoric is optimally utilized to strengthen the delivery of moral and emotional messages. On the other hand, the pragmatic aspect shows the diversity of speech act functions that include giving advice, conveying beliefs, expressing feelings, and creating a psychological impact on the reader.كتاب يا بنتي لعلي الطنطاوي هو عمل مهم غني بالنصائح للنساء، لكنه لم يبحث كثيرا من منظور الأسلوبية والتداولية. تهدف هذه الدراسة إلى تحليل الأساليب اللغوية وأشكال الأفعال الكلامية ووظائفها في كتاب يا بنتي. بناء على ما ذكره أبرامز وهارفم، تركز هذه الدراسة على أربعة جوانب أسلوبية، وهي: الصوتية، والمعجمية، والنحوية، والبلاغية. ثم، استخدمت التداولية لاستكشاف أشكال ووظائف الأفعال الكلامية الموجودة في كتاب يا بنتي. وهذه الدراسة هي بحث مكتبي باستخدام التحليل الوصفي الكيفي. أظهرت نتائج البحث أن كتاب يا بنتي عمل غني بالتنوع في الأساليب اللغوية والأفعال الكلامية. كل عنصر من عناصر الأساليب اللغوية، بدءا من الصوتية، والمعجمية، والنحوية، وحتى البلاغية، تم استخدامه لتعزيز إيصال الرسائل الأخلاقية والعاطفية. ومن ناحية أخرى، أظهر الجانب التداولي تنوعا في وظائف الأفعال الكلامية التي تشمل تقديم النصائح، وإيصال القناعات، والتعبير عن المشاعر، وحتى إحداث تأثير نفسي على القارئات.